ON THE OCCURRENCE OF NEMIPTERUS METOPIAS (BLEEKER, 1852) (NEMIFTERIDAE, PISCES) FROM THE SOUTH WEST COAST OF INDIA - Mohan, Madan; Gopakumar, G (Indian Journal of Fisheries, 2011)
The species of Nemipterus so far reported to occur in the seas aroundIndia are, Nemipterus margtnatus (Valenoiennies), N. hexodon (Quoy >andGaimard), N. japonicus (Bloch), N. luteus (Schneider), N. mesoprion (Bleeker),N. tolu (Val.) and N. delagoae Smith (Day 1878, Weber and De Beaufort1936, and Muilhy Mas). The present authors collected five specimens ofNemipterus metopias (Sleeker) the occurrence of which has not been recordedso far from Indian waters, from Vizhinjam during February 1980 from thecatches by hooks and lines.